2021
DOI: 10.1002/slct.202004393
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functional Alginate‐Polyethylene Polyamine Composite Aerogel Toward Sensing and Extracting Copper Ions in Water

Abstract: In this study, a new type of sodium alginate‐polyethylene polyamine composite aerogel (Alg‐PEMA) was synthesized to detect and remove excess copper ions (Cu2+) in water. First, a classic acylation reaction was used to graft polyethylene polyamine onto alginate, which was then gelatinized in a calcium ion solution and vacuum freeze‐dried to prepare the final Alg‐PEMA adsorbent. Experimental results showed that the as‐prepared Alg‐PEMA can remove 99.2 % of Cu2+ (0.1 mM) in water, and the maximum adsorption capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Some studies have shown that copper ions exist in the central nervous system in the form of cerebrocuprein [9], which has a significant impact on brain development, it has also been linked to Alzheimer's and mad cow disease [10]. At present, on a global scale, the copper content in drinking water in China and Japan shall not exceed 1.0 mg l −1 , no more than 1.3 mg l −1 in the United States, and the European Union limits its content to 2.0 mg l −1 [11][12][13]. And when excessive copper accumulated in our body, copper ions will accumulate in the liver and affect DNA replication and the synthesis of many biological processes, pose a great threat to human health [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that copper ions exist in the central nervous system in the form of cerebrocuprein [9], which has a significant impact on brain development, it has also been linked to Alzheimer's and mad cow disease [10]. At present, on a global scale, the copper content in drinking water in China and Japan shall not exceed 1.0 mg l −1 , no more than 1.3 mg l −1 in the United States, and the European Union limits its content to 2.0 mg l −1 [11][12][13]. And when excessive copper accumulated in our body, copper ions will accumulate in the liver and affect DNA replication and the synthesis of many biological processes, pose a great threat to human health [14].…”
Section: Introductionmentioning
confidence: 99%